A Analisis Tingkat Pengalaman dan Respon MAsyarakat Dalam Menghadapi Bencana Banjir Di Kecamatan Koto Tangah Kota Padang - santi, laras (JURNAL BUANA, 2026)
This study aims to determine (1) the extent of flood prone areas in Koto Tangah District. (2) the level of experience of the people of Koto Tangah Subdistrict in dealing with flood disasters. (3) the level of community response in Koto Tangah Subdistrict in facing flood disasters. This research uses descriptive quantitative method with data collection through questionnaires and interviews, random sampling. The variables used are experience, response and preparedness variables in the face of flood disasters. Determination of the sample using the Slovin formula with a population of residents of Koto Tangah District (203840) and the sample used was 100 samples. Data analysis used the JASP application, then regression analysis was conducted to understand the influencing factor. This study shows that (1) Flood hazards in Koto Tangah Subdistrict, areas with Low flood areas covering 2.21 hectares, Medium covering 2068.59 hectares, High covering 2157.69 hectares and areas that do not experience flooding covering 18044.86 hectares. (2) The results of the regression test between the experience variable and flood preparedness provide results that illustrate a weak but significant relationship at the marginal level (R = 0.196, R2 = 0.038). (3) The linear regression results show that the unstandardized regression coefficient for the response variable is -0.561 with p = 0.0198, which means this relationship is significant, but the negative regression indicates that an increase in the response value tends to be followed by a decrease in preparedness. Keywords: Flood, Experience, Response, Preparedness, JASP